Lipomas of the oral cavity - A. V. Lysenko; A. I. Yaremenko; E. A. Ivanova; E. A. Vereshchagina (Вестник хирургии имени И.И. Грекова)
INTRODUCTION. Lipomas are benign mesenchymal tumors consisting of mature adipocytes. They are classified according to their histological picture, localization in the oral cavity and the type of tissues involved in the pathological process.The OBJECTIVE was to present the clinical case and literature review.MATERIALS AND METHODS. We conducted the search in the PubMed database for the last 86 years (1937–2023) with keywords «oral lipoma» or «tongue lipoma».RESULTS. We reviewed 60 articles with 77 identified lipomas. The most publications were represented by the USA (n=10, 16.39%) and India (n=10, 16.39%). We found out that the average age was 51.38 years (51.38±15.57); and most of them occurred over 50 years old. Lipomas are mainly localized on the mucous membrane of the cheek (n=24, 31.17%), then on the tongue (n=17, 22.8%) and in other places. The most common histological picture was spindle cell lipomas (n=13, 27.66%), followed by fibrolipomas (n=8, 17.02%) and other types.CONCLUSIONS. Lipomas are relatively rare neoplasms of the oral cavity. chronic traumatization of the oral mucosa is the predisposing factor for lipoma development. Preventive examinations every six months is recommended, if a patient has dental constructions. Any formation removed from the oral cavity is subjected to histological verification.